EDUCATION REGULATION FOR EQUALITY: ADDRESSING THE GAP BETWEEN PUBLIC AND PRIVATE SCHOOLS IN INDONESIA - Tobondo, Yuyun Alfasius (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2024)
Inequality between public and private schools in Indonesia's education system is still a complex problem. Differences in regulation, funding, accessibility, and quality of education lead to significant gaps between the two types of schools. This study aims to evaluate the extent to which applied educational policies can support educational equality. The research method used is a qualitative approach with policy analysis and an in-depth literature review. The results of the study show that zoning policies, distribution of subsidies, and the management of education funding have not been fully effective in reducing inequality. Instead, some policies exacerbate disparities in access and quality of education. Key challenges in policy implementation include a lack of regulatory flexibility, imbalances in resource allocation, and differences in managerial capacity between public and private schools. Therefore, a more inclusive and needs-based policy strategy is needed to create a fairer education system. A thorough evaluation of education policy should be carried out to ensure equality of access and quality for all learners in Indonesia.